2010
DOI: 10.2166/wqrj.2010.042
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Laboratory-Scale and Pilot-Scale Attached Growth Ammonia Removal Kinetics at Cold Temperature and Low Influent Carbon

Abstract: A mobile testing center was installed at a lagoon wastewater treatment plant (WWTP) at Terrebonne, Canada to investigate the rate of ammonia removal of attached growth treatment systems at 4°C and at low influent carbon concentrations. The testing center housed two laboratory-scale reactors, a pilot-scale BioStyr system (Veolia Water) and a pilot-scale moving bed bioreactor (MBBR) system (Veolia Water). Although the rates of laboratory-scale and the pilot-scale systems demonstrated that the exposure time to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…The effluent ammonia concentrations in this study were measured as total ammonia, in which the portion of free-phase ammonia as compared to federal regulations would be extremely small at a pH of 7 to 8 (pH range throughout the entire experimental phase). Although the removal rate at 1 °C in this study could not be directly compared to past studies because of a lack of rates of nitrification at 1 °C in the current literature, nitrification rates measured at 4 °C are in accordance with those found in this study (Delatolla et aL, 2011 The discrepancy between the ammonia removal rates of Rl and R2 observed in Figure 2 is not statistically significant and is most likely caused by natural variances inherent to the systems and the analytical methods. However, it should be noted that the mass of biofilm per carrier in both reactors was recorded throughout the study and that Rl demonstrated a slightly larger mass of biofilm per carrier than R2 at 20 and 1 °C.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The effluent ammonia concentrations in this study were measured as total ammonia, in which the portion of free-phase ammonia as compared to federal regulations would be extremely small at a pH of 7 to 8 (pH range throughout the entire experimental phase). Although the removal rate at 1 °C in this study could not be directly compared to past studies because of a lack of rates of nitrification at 1 °C in the current literature, nitrification rates measured at 4 °C are in accordance with those found in this study (Delatolla et aL, 2011 The discrepancy between the ammonia removal rates of Rl and R2 observed in Figure 2 is not statistically significant and is most likely caused by natural variances inherent to the systems and the analytical methods. However, it should be noted that the mass of biofilm per carrier in both reactors was recorded throughout the study and that Rl demonstrated a slightly larger mass of biofilm per carrier than R2 at 20 and 1 °C.…”
Section: Resultssupporting
confidence: 78%
“…Numerous studies and practical experience have identified the effect of low temperatures on nitrifying bacteria as the cause for loss of nitrification (Sharma and Ahlert, 1977;Painter and Loveless, 1983;Salvetti et al, 2006;Zhu and Chen, 2002). Attached growth processes and, specifically, the moving bed biofilm reactor (MBBR) have shown promise in achieving short-term ammonia removal at cold temperatures below 4 8C (Andreottola et al, 2000;Delatolla et al, 2011;Wessman and Johnson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These removal rates indicate that the MBBRs were successful in reducing the concentration of ammonia from septic tank effluent. Houweling et al (2007) and Delatolla et al (2010) showed nitrogen removal rates in the range 0.15-0.28 kg N/m 3 day at temperatures of 4-7°C.…”
Section: Ammonia Removal Rate In Continuous Flow Mbbrmentioning
confidence: 97%
“…K3 biocarriers were selected in this study as they provide a large protected surface area for the biofilm growth and optimal conditions for biological activity when suspended in water (Delatolla et al 2010;Almomani et al 2014). The plastic biocarriers occupied 30 % of the volume of the reactor, allowing for free movement within the reactor aided by the air bubbles created by the diffusors.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation